Ten principles for conservation translocations of threatened wood-inhabiting fungi. (April 2020) - Nordén, Jenni; Abrego, Nerea; Boddy, Lynne; Bässler, Claus; Dahlberg, Anders; Halme, Panu; Hällfors, Maria; Maurice, Sundy; Menkis, Audrius; Miettinen, Otto; Mäkipää, Raisa; Ovaskainen, Otso; et al.
Abstract: Unlike for many other organism groups, conservation translocations of fungi are still rare. Encouraged by recent successful translocations, there is a growing interest in applying this conservation tool to threatened wood-inhabiting fungi. When combined with other conservation or restoration measures, translocation can be an effective measure for preventing further population decline in the short term, and species extinctions in the long term. Translocations can be appropriate for rare and specialist fungal species that occur as small local populations in isolated patches across fragmented landscapes, where there is a low likelihood of successful dispersal between distant host trees that have special qualities and are situated in suitable conditions. As species translocations are a controversial topic, the pros and cons of translocation as a conservation tool for threatened fungi need careful consideration. We highlight the uncertainties and risks that are connected to fungal translocations, and propose ten principles adhering to the precautionary principle.